Mechanical properties of pumpkin seeds - Cabral de Oliveira, Daniel Emanuel; Sarah Gabrielle Sousa Bueno; José Mauro Guimarães Carvalho; José Roberto da Costa Júnior; Osvaldo Resende; Vinicius Soares Costa (Comunicata Scientiae, 2022)
Due to the lack of information on the mechanical properties of pumpkin seeds and the need to develop equipment that can be used more efficiently for its processing, the objective of this project was to study the mechanical properties of commercial pumpkin seeds. Pumpkin seeds (Cucurbita moschata) from the commercial cultivars ‘Rajada Seca Melhorada’ and ‘Jacarezinho’ with moisture content ranging from 0.670 to 0.094 decimal dry basis (db) and 0.923 to 0.033 decimal (db), respectively, were used. The determination of the compressive strength of the seeds was carried out by means of uniaxial compression tests. The seeds were compressed in their natural resting position, at a constant speed (force application rate) of 0.0001 m s-1. The average force for deformations in the ’Rajada Seca Melhorada’ was 43.90 and 0.56 N and for ’Jacarezinho’ between 13.20 and 0.20 N, and the values ​​of the proportional deformity module from 8.05 to 23.68 x 107 N m-2 cultivar ’Rajada Seca Melhorada’ and 2.05 to 21.64 x 107 N m-2 for ’Jacarezinho’. It is concluded that the necessary force for deformation of pumpkin seeds decreases with the increase of the moisture content. There is an increase in the values ​​of the proportional deformity module with the reduction of the moisture content, for the cultivar ‘Rajada Seca Melhorada’ and ‘Jacarezinho’. It can be seen that the seeds of the pumpkin ’Rajada Seca Melhorada’ have a greater resistance to the deformation force in relation to ’Jacarezinho’.